Transcatheter management of combined patent ductus arteriosus and left pulmonary artery stenosis in congenital rubella syndrome: A series of three patients and an insight into case selection for intervention - Mahua Roy; Debasree Gangopadhyay; Noopur Goyel; Amitabha Chattopadhyay; Biswajit Bandyopadhyay (Wolters Kluwer Medknow Publications, 2022)
Transcatheter closure of patent ductus arteriosus (PDA) is now the standard of care with some exceptions. Best treatment for peripheral pulmonary artery (PA) stenosis in small children is still debatable. Surgical augmentation, balloon dilatation, and stenting are the available options with each having its own risks and limitations. Here, we are reporting complete transcatheter management of three cases of congenital rubella syndrome who had PDA and left branch PA stenosis by device closure and stent placement, with successful outcome in two cases and complication, leading to surgery in one. We also share our understanding of case selection for a better outcome.